Tra notariato e letteratura L'edizione critica del Cammino di Dante di ser Piero Bonaccorsi - Bassani, Claudia (Premio Ricerca «Città di Firenze», 2021)
This volume presents the critical edition of Cammino di Dante, the first topo-chronographic summary of Dante's Comedy, written by the Florentine notary, ser Piero Bonaccorsi (1410-1477), for the friar of Santa Croce, Romolo de' Medici. The edition of the text is opened by a bio-bibliographical introduction on the author, that hightlights some new aspects of his notarial career, his literary activity and his relationship with notable figures of his age. The text then presents the seven manuscripts that handed down the Cammino, including four original manuscripts by Bonaccorsi, and analyses their textual relations. The edition offers a critical text based on the codex Riccardiano 1122, the last complete autograph edition, whose unreleased appendix is also published.